Barriers in Implementing the PMTCT in Moretele Sub-District, South Africa: An Exploratory Study - Naude Refilwe Ntsime; Lufuno Makhado; Leepile Alfred Sehularo (SAGE Publishing, 2022)
The Prevention-of-Mother-To-Child Transmission (PMTCT) program was introduced to prevent vertical transmission of HIV from a mother to her infant through pregnancy, labor, and breastfeeding. Therefore, it is critical for the program to be accessible in primary health care facilities across the globe to increase treatment uptake and to eliminate child and maternal mortality rates caused by HIV infections. However, barriers are still being experienced by some nurses while implementing PMTCT around Moretele sub-district in the North West Province (NWP). Hence, this qualitative study explored and described the factors influencing the implementation of PMTCT. A qualitative, exploratory-descriptive design was followed. Ten participants were selected purposively, and each participant was interviewed individually using WhatsApp video calling. All participants were made aware of their voices being recorded; data saturation was reached on the eighth participant as no new information evolved. Data were analyzed using Tesch's method of qualitative data analysis. The findings revealed that factors that influenced PMTCT implementation were due to patient, management, and staff-related factors. Moreover, these factors impacted the provision of effective patient care. The findings of this study show that much still needs to be done to achieve and sustain the PMTCT implementation goal. Therefore, the training of nurses should be of paramount importance. They should be provided and equipped with the necessary resources, support, and encouragement to offer and ensure quality health care. Furthermore, the government should ensure that policies and guidelines are regularly monitored and evaluated.